Arnon Rubin, Facts and Fictions about the Rescue of the Polish Jewry during the Holocaust - Haska, Agnieszka (Zagłada Żydów. Studia i Materiały, 2007)
Arnon Rubin, Facts and Fictions about the Rescue of the Polish Jewry during the Holocaust Tel Aviv Uniwersity Press, Tel Aviv 2003–2004Tom I: Jewish Welfare Services in the Occupied Poland, tom II: The Council for Aid to the Jews – Żegota, tom III: Financial Help for The Jews in the Occupied Poland from Abroad, tom IV: The Panderers of Illusions. The Foreign Citzenship, tom V: The Statistucs of Destruction and Rescue, tom VI: The Kielce pogrom – spontaneity, Provocation or Past of Country-Wide Scheme?